Bank of Finland's long-run forecast framework with human capital - Arto Kokkinen; Meri Obstbaum; Petri Mäki-Fränti (Bank of Finland, 2021)
Population ageing constitutes a central challenge to Finland. Understanding the Finnish economy's likely future trajectory and the key sources of growth is important for the design of policies to counteract these adverse long-term trends. For this purpose, we develop a novel long-run forecast framework based on enodogenous growth theory with human and fixed capital. A central result is a pronounced projected decrease in human capital, substantially weighing on the long-run GDP outlook for Finland. To revert these trends substantial policy efforts are needed. Unless the decline in human capital can be prevented by increasing fertility, skilled immigration, education or employment, even reaching a growth rate of one per cent after the 2040s would require significant measures to increase new fixed capital investments with new technology.
urn:nbn:fi:bof-202112162154
Keywords: E17; E24; O11; 330; Forecasting; GDP; Labour productivity; Human capital; Modern growth theory